Evaluation of Preservice Teachers’ Skills in Solving Non-Routine Mathematical Problems through Various Strategies - Usta, Neslihan (Asian Journal of Education and Training, 2020)
This study aims to investigate how the different solutions, problem-solving strategies, and the number of strategies used by the preservice secondary school mathematics teachers on non-routine mathematical problems change according to grade levels. This study was conducted with 152 preservice teachers studying at the department of elementary mathematics education of a state university located in the Western Black Sea region in Turkey. The purposeful sampling method was used to select the participants. A 12-question test with non-routine problems was used as the data collection tool. Content analysis, one of the qualitative data analysis techniques, was used for analyzing the data. The results indicated that the preservice teachers at each grade level generally proposed single solution and more than half of them had difficulties in finding solutions to the problems. It has been observed that the most used strategies of the preservice teachers are the strategies of reasoning, prediction-control, finding a correlation, formation-testing, systematic listing, drawing, and forming equations in all grade levels.